PELATIHAN TEKNIK HIDROPONIK MELON BAGI KELOMPOK GURU DI KABUPATEN MAJENE - Daud, Firdaus; Taiyeb, A. Mushawwir; Pratiwi, Andi Citra; Azis, Andi Asmawati; Jamaluddin, Asham bin; Marzuki, Nur Intan; Mukminati, Sri (Jurnal Abdi Negeriku, 2024)
Cultivating plants using hydroponic methods promises better plant quality compared to conventional methods. However, the application of this technique is still relatively low among the public, especially in Majene Regency, West Sulawesi Province. Meanwhile, the potential for cultivating plants using hydroponic methods in Majene Regency is significant due to the availability of vast land and supportive environmental conditions. Therefore, this community service activity is conducted to increase public knowledge about hydroponic plant cultivation methods in Majene Regency. The training was held on May 11, 2024, at SMPN 2 Majene, and attended by 25 teachers from various districts in Majene Regency. They were selected based on their communication skills and potential to implement the training to students and the surrounding community. The training utilized lecture, discussion, and hands-on practice methods. Participants' response to the training was highly positive, with the majority feeling assisted by the training activities. Subsequent activities are recommended to integrate more innovative hydroponic techniques. It is hoped that the increase in knowledge and skills will encourage more people to adopt hydroponic methods, thus improving the income of the West Sulawesi community.